WOMEN’S PARTICIPATION IN THE ESTABLISHMENT AND DEVELOPMENT OF HEALTHCARE SERVICES IN THE 1950s–1960s (A CASE STUDY OF THE SURKHANDARYA REGION) - Ubaydullaeva Shahlo Abdullaevna (Journal Park Publishing, 2025)
The article describes the development of the medical field in the region during the 1950s-1960s, the issue of staffing in the organization of the healthcare system, and the participation of female doctors in this process. Additionally, it provides information on the role of female doctors in protecting public health, their involvement in medical services, and their contributions to the further development of medicine in Surkhandarya.
Keywords: Surkhandarya, healthcare, medicine, women, maternal and child health protection, rural outpatient clinics, Denov district, Tatyana E.Arskaya, Anna G.Nizhigorodova, All-Union Congress of Pediatric Doctors, epidemiology department, dermatovenereology diseases.